Purification and Properties of Peroxidase from Prangos ferulacea (Apiaceae) and Investigation of Inhibition by Some Chemicals - Nadaroglu, Hayrunnisa (Asian Journal of Chemistry, 2010)
A peroxidase (POD)-containing fraction was purified from Prangos ferulacea (apiaceae) by (NH4)2SO4 precipitation and anion exchange chromatography. The purification grade obtained was 126.36 yielding 41.8 % of the enzyme activity. The molecular weight was estimated to be 40 kDa by gel filtration. It has an optimum pH of 5 and exhibited high pH and thermal stabilities. Km for guaiacol and ABST were 1.347 and 1 mM, respectively. The optimal temperature was 30 ºC. The I50 values for KSCN and NaN3 were 0.750 mM, 1.321 mM in Prangos ferulacea (Apiaceae) CA, respectively.